Requirements and Test Stand Development for ERS Pantographs - Alexander Prinz; Kil Young Lee; Abhishek Gupta; Dietmar Göhlich; Sangyoung Park (World Electric Vehicle Journal)
Electric road systems (ERSs) are a promising solution for electrifying heavy-duty freight transport by providing traction and charging power from the power lines installed along the road. Development of ERSs has been accelerated in the last decade, and several pilot projects have been successfully implemented, proving the high level of maturity that the technology has achieved. One crucial step that could be initiated before a rollout is the standardization and certification of ERS infrastructure and system components. For instance, pantographs for overhead ERSs face unique challenges, in that the power transfer should be safe and reliable in the presence of dynamic longitudinal and lateral movements of the vehicle. To tackle this problem, we outline the requirements for overhead ERSs and ERS pantograph testing. Among the key requirements are the rising and lowering times, response to lateral maneuvers, such as lane changes, and high electrical current during stillstand. We introduce our developed test stands capable of testing various aspects of an ERS pantograph. The lateral test stand was developed to test basic functionalities and simulate lateral movements. A second test stand was implemented, to test high currents and the subsequent temperature development. Furthermore, a digital test stand used for planning, design, and modeling is introduced.